Tissue adaptation of CD4 T lymphocytes in homeostasis and cancer - Pereira, Marina V. A.; Galvani, Rômulo G.; Gonçalves-Silva, Triciana; de Vasconcelo, Zilton Farias Meira; Bonomo, Adriana (Frontiers in Immunology, 2024)
The immune system is traditionally classified as a defense system that can discriminate between self and non-self or dangerous and non-dangerous situations, unleashing a tolerogenic reaction or immune response. These activities are mainly coordinated by the interaction between innate and adaptive cells that act together to eliminate harmful stimuli and keep tissue healthy. However, healthy tissue is not always the end point of an immune response. Much evidence has been accumulated over the years, showing that the immune system has complex, diversified, and integrated functions that converge to maintaining tissue homeostasis, even in the absence of aggression, interacting with the tissue cells and allowing the functional maintenance of that tissue. One of the main cells known for their function in helping the immune response through the production of cytokines is CD4 + T lymphocytes. The cytokines produced by the different subtypes act not only on immune cells but also on tissue cells. Considering that tissues have specific mediators in their architecture, it is plausible that the presence and frequency of CD4 + T lymphocytes of specific subtypes (Th1, Th2, Th17, and others) maintain tissue homeostasis. In situations where homeostasis is disrupted, such as infections, allergies, inflammatory processes, and cancer, local CD4 + T lymphocytes respond to this disruption and, as in the healthy tissue, towards the equilibrium of tissue dynamics. CD4 + T lymphocytes can be manipulated by tumor cells to promote tumor development and metastasis, making them a prognostic factor in various types of cancer. Therefore, understanding the function of tissue-specific CD4 + T lymphocytes is essential in developing new strategies for treating tissue-specific diseases, as occurs in cancer. In this context, this article reviews the evidence for this hypothesis regarding the phenotypes and functions of CD4 + T lymphocytes and compares their contribution to maintaining tissue homeostasis in different organs in a steady state and during tumor progression.